2009
DOI: 10.4161/psb.4.2.7872
|View full text |Cite
|
Sign up to set email alerts
|

Electrical signaling, stomatal conductance, ABA and Ethylene content in avocado trees in response to root hypoxia

Abstract: Abbreviations: ABA, abscisic acid; ACC, 1-aminocyclopropane-1-carboxylic acid; AP, Action Potential; ΔV L-S , voltage differences between the base of the stem and the leaf petiole; ΔV l-b , voltage differences between leaf zone and base of the trunk; gs, stomatal conductance; PPF, photosynthetic photon flux; VP, Variation Potential

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 34 publications
3
32
1
10
Order By: Relevance
“…Orders of magnitude of the observed EP variation in those studies were similar to values observed by other authors (Fromm, 2006;Davies, 2006). Electric potential variations observed in avocado trees in response to decreased soil water content have been associated with a decrease in stomata conductance (gs) (Gil et al, 2009), indicating that stomata closure might be induced or at least associated with an electrical signal that travels through the phloem at a speed of 2.4 cm min -1 . Larger changes in electric potential behavior have been detected in response to drought compared to watering.…”
Section: Wwwintechopencomsupporting
confidence: 70%
See 3 more Smart Citations
“…Orders of magnitude of the observed EP variation in those studies were similar to values observed by other authors (Fromm, 2006;Davies, 2006). Electric potential variations observed in avocado trees in response to decreased soil water content have been associated with a decrease in stomata conductance (gs) (Gil et al, 2009), indicating that stomata closure might be induced or at least associated with an electrical signal that travels through the phloem at a speed of 2.4 cm min -1 . Larger changes in electric potential behavior have been detected in response to drought compared to watering.…”
Section: Wwwintechopencomsupporting
confidence: 70%
“…In most of our publications, electrical potentials are monitored continuously using own designed nonpolarizable Ag/AgCl microelectrodes inserted into different positions along the trunk; microelectrode characteristics have been reported by Gurovich & Hermosilla (2009), Gil et al (2009, Oyarce & Gurovich (2011), and consist on a 0.35 mm-diameter silver wire (99.99% Ag), chlorated in a solution of HCl 0.1N for 30 s using a differential voltage of 2.5 V, to obtain an Ag/AgCl coating, which is inserted in a stainless steel hypodermic needle, 0.5 mm in diameter, filled with a KCl 3M solution; both needle ends are heat-sealed with polyethylene. Electrodes were inserted into the trunk using a low velocity electric microdriller, with a barbed microreel, penetrating the phloematic and cambium tissue; needle tip was further inserted into the xylematic tissue, 0.5-0.75 cm, by mechanical pressure.…”
Section: Plant Electrophysiology Research Technology and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant gene sets, which were enriched in up-regulated genes, were related to plant-type cell wall loosening, an essential step in guard cell swelling (Wei et al, 2011). In down-regulated genes, there were several significant gene sets related to the defense responses for immunity, hypoxia, and ozone, which also influence stomatal responses or gas exchange (Heath, 1994;Melotto et al, 2006;Gil et al, 2009). Microarray analysis demonstrated that these gene expression differences may be related to the differences in stomatal aperture between Me-0 and tetraploid Col evaluated in Figure 3.…”
Section: The Difference In Stomatal Aperture Causes the Difference Inmentioning
confidence: 99%